Adaptive speed and separation monitoring based on switching of safety zones for effective human robot collaboration. (October 2022) - Karagiannis, Panagiotis; Kousi, Niki; Michalos, George; Dimoulas, Konstantinos; Mparis, Konstantinos; Dimosthenopoulos, Dimosthenis; Tokçalar, Önder; Guasch, Toni; Gerio, Gian Paolo; Makris, Sotiris
Highlights: Design of dynamically switched safety zones which are used to monitor human presence Implementation of safety architecture using safety sensors, safety PLC and robot's controller Use the status of the safety zones to adapt robot behaviour based on the signals received Ensure safe co-existence and collaboration of human operators with industrial robots Abstract: This paper presents the design and deployment of a system that enables the safe cooperation and interaction of human operators with industrial robots. Dynamically switched safety zones are used to monitor human presence and respectively adapt robot behavior, namely speed and movement status. An overhead safety camera system is used to identify moving objects within each zone and produce warning and stop signals which are used to regulate the behavior of the robot, slowing it down and stopping it respectively. Based on the real time position reporting of the robot, continuous switching between zone configurations is achieved. This leads to a more efficient speed and separation monitoring process, as defined by ISO/TS 15066, EN-ISO 10218-1 and EN ISO 10218-2, compared to a fixed fence solution. Unlike the case of virtual fences which are currently implemented using light barriers, this approach allows humans to use more workspace from the robot while ensuring separation. The control architecture design and the implementation of the system on a pilot cell inspired from the automotive industry are presented in this paper, as well..